Integration into treatment programs for children with autism spectrum disorder vision and application - Nashaat Abdelaziz, Abdelqader Baioumy; Ahmad Abddllah, Abu Sini; Mallak Sami, Abu Sini (2019)
Autism spectrum disorder impairs the normal growth of children in the fields of social and emotional thinking and interaction and verbal and nonverbal communication skills, thus affecting their ability to communicate with others and not to interact and integrate with their social environment, often resulting in hostile behaviors or self-harming and abusive responses Others. Children with autism spectrum disorder need to diversify into therapeutically approaches; A single treatment method may not be effective in treating all types of disorders and problems in this sample of children. Therefore, this paper seeks to present the vision of integration and the conclusion of its applications in the treatment programs provided to children with autism spectrum disorder through the integration of theory Pivotal response and Higashi Method, The results concluded that the integration of treatment programs for children with autism spectrum disorder is a necessary and effective therapeutic intervention in the development of social interaction skills, the mitigation of unwanted behaviors, the integration of children with disorders Autism spectrum in the surrounding environment, as recommended by the research to build complementary therapeutic programs and test their effectiveness and impact on this group of children.